Interplay of modernity, symbolism, and religious practice in Cirebon’s death rituals - Nurwati, Nunung; Yunita, Desi; Amanatin, Elsa Lutmilarita; Wibowo, Hery; Bustami, Mohammad Reevany (SIMULACRA: JURNAL SOSIOLOGI, 2025)
This study examines the persistence of death rituals in Cirebon amid the pressures of modernity, focusing on how these practices continue to hold deep social and spiritual significance within the community. The research explores how changing values and economic challenges, particularly concerning food preparation and distribution during post-funeral events such as tahlilan and slametan, reflect tensions between religious teachings that discourage wastefulness and local beliefs surrounding purity and respect for the deceased. Employing a qualitative case study design, fieldwork was conducted in Trusmi Village, Cirebon, through in-depth interviews and participant observation involving ritual custodians (kuncen), family members, community leaders, and elders. Data were analyzed thematically via Blumer’s social action theory to interpret how symbols, social meanings, and modernization interact in shaping ritual practices. Findings reveal that while death rituals maintain their function as expressions of religiosity and social solidarity, modern consumerist tendencies have transformed certain practices into displays of prestige, often leading to food waste. The study calls for cultural adaptation and education to align these traditions with Islamic principles of moderation (wasatiyyah) and sustainability, reducing waste while reaffirming the rituals’ essence as expressions of piety, compassion, and solidarity, ensuring they remain spiritually meaningful and socially relevant in Cirebon society.